'Cut Pollution, Create Jobs? Yeah, Nah': partisan effects on environmental protest in Aotearoa New Zealand. (2nd September 2017) - O'Brien, Thomas
ABSTRACT: Protest is a tool that social movements can use to express discontent and present claims to those in power. In New Zealand, campaigns around native forest protection, genetic engineering, mining and offshore oil exploration have mobilised numerous participants, forcing the state to acknowledge public concerns and, in some cases, effect change of course. However, impact of the ideological orientation of the governing party on environmental protest behaviour is less well understood. The aim of this paper is to identify how political opportunities and threats in the protest arena are shaped by changes in the electoral arena. The methodology of protest event analysis is used to identify environmental protest under the left-wing Labour (1999–2008) and right-wing National (2008–2017) governments. Findings suggest that the orientation of the governing party is important in shaping opportunities, illustrated by periods of dominance of the electoral arena by the National Party leading to a corresponding intensification of mobilisation in the protest arena.